Impact of migration and population aging on economic growth in the Republic of Croatia - Vesna Buterin; Barbara Fajdetić; Martina Mrvčić (Ekonomski Vjesnik, 2022)
Purpose: Migrations are a complex economic variable that is highly influenced by conditions such as social, societal, economic, political, environmental, and the like. The preferences of the population vary and in accordance with their own needs, the population decides to migrate. Many economies of the world are facing the problem of out-migration of the young population. Moreover, the elderly population is increasing as a percentage of the total population. The aim of this research is to show the gender and age structure of the population, the state of migration and the impact on the economic growth in the Republic of Croatia.